Analyzing the Impact of Hybrid Working Practices and Online Recruitment Strategies on Employee Performance and Organizational Effectiveness - Qodariah, Qodariah; Ramadhan, Tubagus Guruh (Dinasti Publisher, 2026)
The rapid advancement of digital transformation has encouraged organizations to adopt hybrid working practices and online recruitment strategies as key components of contemporary human resource management. These approaches are expected to improve employee performance while enhancing organizational effectiveness in increasingly dynamic business environments. This study aims to analyze the impact of hybrid working practices and online recruitment strategies on employee performance and organizational effectiveness. The study employed a Narrative Literature Review (NLR) approach by synthesizing findings from peer-reviewed journals, books, conference proceedings, and research reports published between 2015 and 2025. Data were collected from reputable academic databases and analyzed using narrative analysis to identify recurring themes, patterns, and research gaps. The findings indicate that hybrid working practices positively influence employee performance through improved work-life balance, employee well-being, autonomy, and flexibility. Meanwhile, online recruitment strategies enhance employee performance and organizational effectiveness by improving talent acquisition quality, employee-job fit, recruitment efficiency, and access to broader talent pools. Furthermore, the integration of hybrid work and digital recruitment supports organizational agility, resilience, competitiveness, and long-term sustainability. The study highlights the strategic importance of adopting integrated digital HR practices to optimize organizational performance in the digital era.